Human forkhead box protein 3 gene variants associated with altered susceptibility to idiopathic recurrent pregnancy loss: A retrospective case‐control study. (16th May 2022) - Bahia, Wael; Zitouni, Hedia; Kanabekova, Perizat; Bauyrzhanova, Zhansaya; Shaimardanova, Moldir; Finan, Ramzi R.; Aimagambetova, Gulzhanat; Almawi, Wassim Y.
Abstract: Background: The pathogenesis of recurrent pregnancy loss (RPL) is multifactorial and not completely elucidated. Dysregulated immunity was implicated with RPL, in which regulatory T cells (Tregs) are key. As Tregs development and function are regulated by forkhead box P3 (FOXP3) transcription factor, and as FOXP3 expression is genetically determined, a role for FOXP3 polymorphisms in RPL pathogenesis was suggested. Aim: To investigate the association of rs2294021, rs2232365, rs3761548, and rs141704699 FOXP3 variants with idiopathic RPL in Lebanese women. Methods: This retrospective case‐control study included 386 RPL cases and 398 age‐matched control women. Logistic odds ratios (OR) were estimated with 95% confidence interval after adjustment; a significance value of P <.05 was set. Results: Significantly lower rs22944021 and rs2232365 minor allele frequency (MAF) was found in patients with idiopathic RPL in comparison with the control group. Furthermore, statistically significantly lower frequency of heterozygous and homozygous rs2294021 and rs2232365 genotypes was seen in controls, while significantly lower rs3761548 heterozygous genotype frequencies were found in the patient group. Obesity, antihypertension treatment, smoking, positive RPL family history, abortion state, and infertility treatment correlated negatively with rs2294021, while rs2232365 negatively correlated with obesity, and rs3761548 negatively correlated with infertility treatment. Marked linkage disequilibrium (LD) was noted among FOXP3 SNPs, with TGCC and CGAC haplotypes being positive, while CAAC, CACC, and TGAC haplotypes being negatively associated with RPL risk. Except for CGAC, the association of these haplotypes with RPL persisted after adjustment. Conclusion: FOXP3 gene variants and haplotypes are associated with altered incidence of RPL, proposing the role of Treg in RPL pathogenesis.